Exceptional rainfall characteristics related to erosion risk in semiarid Tunisia - Jebari, S.; Berndtsson, R.; Bahri, Akissa; Boufaroua, M. (2008)
The Tunisian Dorsal area is representative of the semiarid Mediterranean region in terms of water resources availability as well as exceptional rainfall characteristics, runoff generation, and soil loss risk. In this context, soil properties, surface management practices together with highly intensive rainfall make the soils vulnerable to erosion. If the exceptional rainfall characteristics are linked to different erosion types, the erosion risk could be evaluated in a simple and straightforward way. In this regard, a short time-scale rainfall data base from the Dorsal area was analysed in the paper. The procedure used involves finding a representative duration between 1-60 min for the exceptional rainfall characteristics. Rainfall intensities of different return periods are then related to the different erosion types. The identified exceptional rainfall durations between 1-60 min were analyzed in terms of number of events, depth, average intensity and maximum intensity. Results show that the 15-min duration maximum intensity can be used to evaluate erosion risk based on soil erosion type. The developed methodology can be used to evaluate erosion risk in semiarid regions based on exceptional rainfall characteristics. In practical terms the results can be used to better manage catchments that are vulnerable to soil erosion.